Crystal field aspects of the vibrational spectra of some metal complexes of tropolone and nitrogen donor ligands - Hulett, Leslie Graham (Department of Chemistry, 2016)
Previous work on crystal field aspects of the vibrational spectra of metal β-ketoenolates has been extended here to metal tropolonate complexes. The crystal field trends have been used to assist in the assignment of metal sensitive vibrations to the transition metal tropolonate complexes. A study has been made of the effects of spin state and Jahn-Teller distortion on the vibrational spectra of the metal tropolonates. Of particular interest is the octahedral divalent metal tropolonate adducts, where the distortion of the copper complex is small, and the metal 2-thiotroponates where the Jahn-Teller- distortion is absent. The spectra of the lanthanide tropolonates are of interest, as a plot of the metal sensitive vibrations show the 'double-humped' curve indicating that crystal field effects are present in the lanthanide ions. This has not previously been shown. Further, from the vibrational spectra of the various lanthanide tropolonates, various conclusions are made regarding structure. The non-transition metal tropolonates provide a system devoid of crystal field effects and afford the opportunity to investigate the influence of other factors on the vibrational spectra. Of interest is the strong influence of the ionic radius and ionization potential on the metal sensitive vibrations and the remarkably small influence of the mass of the metal ion on these vibrations. Although the vibrational spectra of complexes of ethylenediamine and N- substituted ethylenediamines were studied, difficulty with, assignment of the metal sensitive vibrations and the complicating influence of substituents on the spectra, prevents any observations made, from being conclusive.